Pragmatic Challenges in Politeness Expressions Among Iraqi EFL Students: Tantangan Pragmatis dalam Ekspresi Kesopanan di Kalangan Mahasiswa EFL Irak - Al'aa Ali Hasan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The ability to use politeness expressions effectively in a second language is a crucial component of communicative competence. Specific Background: Recent studies have highlighted challenges language learners face in expressing themselves appropriately in different cultural contexts. Knowledge Gap: Despite the importance of pragmatic competence, there is a lack of research on how Iraqi university students, learning English as a foreign language (IEFL), navigate politeness phrases in real-life situations. Aims: This study aims to examine the pragmatic realization of politeness expressions such as requests, refusals, apologies, offers, and gratitude among IEFL students. Results: Using Discourse Completion Tests (DCTs), the study found that Iraqi students face significant challenges in pragmalinguistic realization of politeness expressions compared to American native speakers. Cultural differences were identified as a key factor contributing to these challenges, with Iraqi students often using expressions considered impolite in English-speaking cultures. Novelty: This study contributes new insights into the pragmatic difficulties faced by IEFL students in Iraqi cultural contexts. Implications: The findings suggest that language teaching should focus on developing pragmatic competence by providing contextual and culturally relevant teaching methods, helping students navigate speech conventions more effectively. Highlights: Pragmalinguistic challenges: Iraqi students struggle with polite English expressions. Cultural influence: Cultural differences affect polite expression use. Teaching implications: Focus on pragmatic competence in language education. Keywords: pragmatics, politeness expressions, English as a foreign language, cultural differences, communicative competence